Clinical importance of parent ratings of everyday cognitive abilities in children with learning and attention problems. - Dewey D; Crawford SG; Kaplan BJ (Journal of Learning Disabilities)
This study addressed two issues: first, whether parental reports contribute information over and above a standardized psychometric assessment, and second, whether parental reports of everyday cognitive functioning might be useful in distinguishing between children with reading disabilities (RD), attention-deficit/hyperactivity disorder (ADHD), and combined ADHD + RD. Parent-reported information on 159 children with learning or attention problems was obtained using a questionnaire called the Parent Ratings of Everyday Cognitive and Academic Abilities (PRECAA). Psychometric information used for comparison included the Woodcock-Johnson Psychoeducational Battery-Revised, the Bruininks-Oseretsky Test of Motor Proficiency-Short Form, the Vocabulary and Block Design subtests of the Wechsler Intelligence Scale for Children, 3rd edition, and the Developmental Test of Visual-Motor Integration. The PRECAA was found to be sensitive to group differences between children with RD and children with ADHD and combined ADHD + RD. Its inclusion resulted in a significant increase in the number of children correctly classified compared to the use of psychometric measures alone. The PRECAA correctly classified more children (66%) than did the standard psychometric measures (50%). In fact, a very high percentage of children with ADHD (81%) were correctly classified using the PRECAA. These findings suggest that the PRECAA may be a useful aid to clinicians in the identification of children with learning and attention problems.